Pengaruh Kualitas Audit, Profitabilitas, Solvabilitas, dan Ukuran Perusahaan Terhadap Audit Delay - Puspitasari, Septi Maharani; Adi, Suyatmin Waskito (Jurnal EMT KITA, 2024)
This research aims to examine the factors that influence audit delays in primary consumer goods companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. The factors studied include audit quality, profitability, solvency, and company size. Research data was obtained from company financial reports taken via www.idx.co.id. The analytical method used is multiple linear regression with the help of the SPSS program. The analysis results show that audit quality and solvency have a significant influence on audit delay. High audit quality tends to reduce the possibility of audit delays, while high solvency increases the possibility of audit delays. On the other hand, profitability and company size do not have a significant effect on audit delay. The findings show that audit quality and solvency influence audit delay, while profitability and company size do not. The implications of these findings can help practitioners understand the dynamics of audit delay better